STRATEGI PENGEMBANGAN KUE KERING LOKAL SEBAGAI UPAYA MENINGKATKAN EKONOMI KREATIF DI DESA GALUNG KECAMATAN ULAWENG - Ananda Putri; Ismail Keri; Munawarah Munawarah (Universitas Persada Indonesia YAI, 2026)
This study aims to analyze the development strategy of local dry cake products (nastar, putri salju, and rambutan cookies) as an effort to enhance the creative economy in Galung Village, Ulaweng District, Bone Regency. The objectives of this study include: (1) analyzing product innovation, (2) analyzing packaging innovation, and (3) analyzing the marketing strategy of local dry cake products. This study employs a qualitative approach with a descriptive research design. Data were collected through semi-structured interviews and documentation, while data analysis was conducted through data reduction, data presentation, analysis, and conclusion drawing. The results of the study indicate that: (1) product innovation is carried out through the development of product variations, flavor variants, the utilization of local raw materials, as well as improvements in product quality and appearance; (2) packaging innovation is carried out through the use of more attractive packaging, product labeling, and the inclusion of product information to increase consumer appeal and trust; and (3) marketing strategies are implemented through direct marketing, word-of-mouth promotion, and the utilization of social media to expand market reach. Therefore, product, packaging, and marketing innovations need to be continuously developed to enhance product competitiveness and strengthen the creative economy of the Galung Village community